Hybridity in peacebuilding and development: a critical approach. Issue 4 (4th July 2017) - Forsyth, Miranda; Kent, Lia; Dinnen, Sinclair; Wallis, Joanne; Bose, Srinjoy
Abstract: The concept of hybridity has been used in numerous ways by scholars across a range of disciplines to generate important analytical and methodological insights. Its most recent application in the social sciences has also attracted powerful critiques that have highlighted its limitations and challenged its continuing usage. This article, which introduces the collection on Critical Hybridity in Peacebuilding and Development, examines whether the value of hybridity as a concept can continue to be harnessed, and how its shortcomings might be mitigated or overcome. Specifically, we seek to demonstrate the multiple ways to embrace the benefits of hybridity, while also guiding scholars through some of the potentially dangerous and problematic areas that we have identified through our own engagement with the hybridity concept and by learning from the critiques of others. This pathway, which we have termed 'critical hybridity', identifies eight approaches that are likely to lead scholars towards a more reflexive and nuanced engagement with the concept.